Exact greybody factors for the brane scalar field of five-dimensional rotating black holes - Young-Hwan Hyun; Yoonbai Kim; Seong Chan Park (Journal of High Energy Physics, 2019)
Abstract We study scalar perturbations of the five-dimensional rotating black holes and find an exact solution giving exact description of the Hawking radiation. Mathematically, the full solution for this spin-zero field is expressed in terms of the prolate spheroidal wave function with complex parameters. By using the spheroidal joining factor, we write the corresponding boundary condition and greybody factors. We also check that the exact result reproduces the low frequency limit of the greybody factor and shows good agreement with the known numerical results.